Program Pengembangan SDM Berbasis Pelayanan Prima untuk Meningkatkan Kepuasan Konsumen di Rumah Oblong - Fauzan Fauzan; Shara Franda Juwita; Amada Aulia Sakinah; Putri Mega Amanda; Melia Susanti; Viola Peza Agustri; Patriyani Patriyani; Tarisa Putri Ayu Tama; Rheva Rislika Savela; Ardiandi Aidil Syahputra; Alda Violah; Amanda Saputra; Fajri Kurnia (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
A human resource development program based on excellent service was implemented at Rumah Oblong to enhance employee service quality, thereby boosting customer satisfaction and supporting business sustainability. The initiative was prompted by suboptimal service quality, evidenced by inconsistencies in customer service approaches and a lack of uniformity in employee interactions with consumers. The program employed a participatory approach comprising several stages: needs identification (via observation, interviews, and questionnaires), a two-day excellent service training session, two months of mentoring and monitoring, and a final evaluation involving observation, interviews, and assessments of changes in service behavior. The program’s novelty lies in its integrated, continuous approach combining training, mentoring, and monitoring tailored to Rumah Oblong’s operational characteristics. Results indicate improved employee competence, reflected in shifts from "fairly good" to "good" regarding understanding, from "moderately agile" to "agile" regarding work performance, from "moderately solution-oriented" to "solution-oriented" regarding problem-solving, and from "moderately innovative" to "innovative" regarding service innovation; meanwhile, friendliness and service reliability remained at a "good" level. These changes resulted in more consistent service and a more pleasant shopping experience for customers. Thus, the excellent service-based human resource development program proved effective in enhancing service quality at Rumah Oblong.